Morphometric analysis of Doce River watershed, Goiás, Brazil - Silva, Leandro Ferreira da; Oliveira, Marcos Vinícius de Melo; Nuñez, Daniel Noe Coaguila (Brazilian Journal of Science, 2023)
The watershed is very important to draw up a plan of the environment that are the major social and natural factors. This course conclusion work aimed to carry out a morphometric analysis of the Doce River watershed. The methodology used was indexes intended for this purpose. It consists of several units where all the hydrological procedures that distinguish the total water cycle. In this sense, the physical qualities of the basins must modulate the amplitude of these hydrological processes and cases that cause damage, as well as floods, and define the entire water availability of the large basin. The Doce River hydrographic basin presents degradation and cases of floods, and many water resources. Thus, a morphometric analysis of the fundamental sub-basins of the Rio Doce was carried out. It concludes with the main part of the hydrographic characterization of the Doce River basin, showing its importance.